Evaluasi Efektivitas Pemanfaatan Aplikasi E-Musrenbang Berbasis Geospasial dalam Pembangunan di Kota Bontang - Eko Mashudi; Enos Paselle (Syntax Corporation Indonesia, 2024)
The aim of this research is to evaluate how well the e-Musrenbang application performs in the North Bontang Regency area in terms of development planning. The importance of implementing e-Government and Electronic-Based Government Systems in development planning is the driving force for this research. e-Musrenbang, an application with a geographical focus, is a method used to help communities get involved in development. With a research focus on North and South Bontang Regencies, this research uses qualitative methodology. The research objects are represented by Guntung Village and Tanjung Laut Indah Village. Using Budiani's theory, this research focuses on the characteristics of goal setting, socialization, target accuracy, and monitoring. Utilizing secondary data, interviewing relevant informants, and observation are the methods used for data collection. The research findings show how well the e-Musrenbang application is able to increase community involvement in planning and development in North Bontang District and South Bontang District. In this case, the public can convey their ambitions more easily online thanks to this program, which also helps the government in regulating and monitoring these aspirations. In addition, the application of geospatial technology makes development planning easier and more precise and focused. However, there are several shortcomings in this research, such as research topics that are limited to two different sub-districts and data collection techniques that only use qualitative techniques. Therefore, to have a more thorough understanding of the usability of this application, it is recommended that future research integrate qualitative and quantitative methodologies.